COVID-19 and Pediatric Asthma: Clinical and Management Challenges - Boechat, José Laerte (Int J Environ Res Public Health, 2021)
Asthma is the most frequent chronic condition in childhood and a current concern exists about asthma in the pediatric population and its risk for severe SARS-CoV-2 infection. Although all ages can be affected, SARS-CoV-2 infection has lower clinical impact on children and adolescents than on adults. Fever, cough and shortness of breath are the most common symptoms and signs in children; wheezing has not been frequently reported. Published studies suggest that children with asthma do not appear to be disproportionately more affected by COVID-19. This hypothesis raises two issues: is asthma (and/or atopy) an independent protective factor for COVID-19? If yes, why? Explanations for this could include the lower IFN-α production, protective role of eosinophils in the airway, and antiviral and immunomodulatory proprieties of inhaled steroids. Additionally, recent evidence supports that allergic sensitization is inversely related to ACE2 expression. Obesity is a known risk factor for COVID-19 in adults. However, in the childhood asthma–obesity phenotype, the classic atopic Th2 pattern seems to predominate, which could hypothetically be a protective factor for severe SARS-CoV-2 infection in children with both conditions. Finally, the return to school activities raises concerns, as asymptomatic children could act as vectors for the spread of the disease. Although this is still a controversial topic, the identification and management of asymptomatic children is an important approach during the SARS-CoV-2 epidemic. Focus on asthma control, risk stratification, and medication adherence will be essential to allow children with asthma to return safely to school.